Standards for the care of people with cystic fibrosis (CF): A timely and accurate diagnosis - Castellani, Carlo; Simmonds, Nicholas J.; Barben, Juerg; Addy, Charlotte; Bevan, Amanda; Burgel, Pierre-Regis; Drevinek, Pavel; Gartner, Silvia; Gramegna, Andrea; Lammertyn, Elise; Landau, Eddie C.; Middleton, Peter G.; et al. (Journal of cystic fibrosis, 2023)
There is considerable activity with respect to diagnosis in the field of cystic fibrosis (CF). This relates primarily to developments in newborn bloodspot screening (NBS), more extensive gene analysis and improved characteri-sation of CFTR-related disorder (CFTR-RD). This is particularly pertinent with respect to accessibility to variant -specific therapy (VST), a transformational intervention for people with CF with eligible CFTR gene variants. This advance reinforces the need for a timely and accurate diagnosis. In the future, there is potential for trials to assess effectiveness of variant-specific therapy for CFTR-RD. The guidance in this paper reaffirms previous standards, clarifies a number of issues, and integrates emerging evidence. Timely and accurate diagnosis has never been more important for people with CF.
Gesehen am 18.03.2023
Online verfügbar: 27 September 2023, Artikel verfügbar: 1 Dezember 2023